MENINGKATKAN HASIL BELAJAR KETERAMPILAN BERMAIN TENIS MEJA MENGGUNAKAN DINDING PANTUL KELAS V SD NEGERI 002 BABULU - AGUNG NURHADI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2022)
The background in this study is that there are still many students who have not been able to perform the basic techniques of playing table tennis, besides that many of the students have not yet completed reaching the Minimum Completeness Criteria (KKM) with a standard value of 70. This study aims to see the results of applying the method used used in improving the skills of playing table tennis in fifth grade students of SD Negeri 002 Babulu. The application in the learning process with bouncing wall media can improve learning outcomes of table tennis playing skills. The purpose of this study was to see the results of the application of the method used and to determine the improvement of learning outcomes of table tennis playing skills through the application of modification of learning tools using bouncing walls. This type of research is classroom action research which is carried out in two cycles. Each cycle has 4 steps, namely: planning, implementation, observation and reflection. The data sources for this study were the fifth grade students of SD Negeri 002 Babulu, totaling 27 students consisting of 16 female students and 11 male students. Data collection techniques with observation, ability tests and learning outcomes of table tennis playing skills. The data analysis technique used in this research is descriptive qualitative statistics. Based on the results of the study that the learning process through the application of modification of learning tools can improve learning outcomes of table tennis playing skills. From the results of the analysis of the data obtained, there was a significant increase from cycle I and cycle II. Learning outcomes in the first cycle in the complete category were 44.44% and in the second cycle there was an increase in student learning outcomes in the complete category by 88.89% ABSTRAKLatar belakang dalam penelitian ini adalah masih banyak peserta didik yang belum mampu melakukan teknik dasar bermain tenis meja, selain itu banyak dari peserta didik yang belum tuntas mencapai Kriteria Ketuntasan Minimal (KKM) dengan standar nilai 70. Penelitian ini bertujuan untuk melihat hasil penerapan metode yang digunakan dalam meningkatkan keterampilan bermain tenis meja pada peserta didik kelas V SD Negeri 002 Babulu. Penerapan dalam proses pembelajaran dengan media dinding pantul dapat meningkatkan hasil pembelajaran keterampilan bermain tenis meja.Tujuan dari penelitian ini adalah untuk melihat hasil penerapan metode yang digunakan dan untuk mengetahui peningkatan hasil belajar keterampilan bermain tenis meja melalui penerapan modifikasi alat pembelajaran menggunakan dinding pantul. Jenis penelitian ini adalah penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Setiap siklus mempunyai 4 langkah yaitu : perencanaan, pelaksanaan, observasi dan refleksi. Sumber data penelitian ini adalah peserta didik kelas V SD Negeri 002 Babulu yang berjumlah 27 peserta didikyang terdiri atas 16 peserta didik perempuan dan 11 peserta didik laki-laki. Teknik pengumpulan data dengan observasi, tes kemampuan dan hasil belajar keterampilan bermain tenis meja. Teknik analisis data yang digunakan dalam penelitian ini adalah statistik deskriptif kualitatif. Berdasarkan hasil penelitian bahwa proses pembelajaran melalui penerapan modifikasi alat pembelajaran dapat meningkatkan hasil belajar keterampilan bermain tenis meja. Dari hasil analisis data yang diperoleh terjadi peningkatan yang signifikan dari siklus I dan siklus II. Hasil belajar pada siklus I dalam kategori tuntas adalah 44,44% dan pada siklus II terjadi peningkatan hasil belajar peserta didikdalam kategori tuntas sebesar 88,89%